2018
DOI: 10.6018/eglobal.18.1.302991
|View full text |Cite
|
Sign up to set email alerts
|

Gestión del dolor de niños y adolescentes durante el período post- trasplante de células-tronco hematopoyéticas: una revisión integradora

Abstract: Este estudo teve como objetivo identificar, em produções científicas, as estratégias utilizadas para o gerenciamento da dor de crianças e adolescentes no período pós-transplante de células-tronco hematopoéticas. Para tanto, utilizou-se como metodologia a revisão integrativa da literatura a partir das seguintes fontes de informação: MEDLINE, LILACS, ScIELO, BDENF, SCOPUS, Web of Science e Plataforma de periódicos CAPES. Os descritores utilizados para a busca foram: pain, pain management; pain pediatric; hematop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…In a study with post-transplant children and adolescent, pain was found to be the most frequent and debilitating symptom in the context of HPST (24) , and, in this study, it was mostly associated with oral mucositis, although it was also related with abdominal pain, to the insertion of the semi-implanted central venous catheter (SICVC), and to the graft-versus-host disease (GVHD). These results are similar to the findings of another study with a similar population, which showed that the pain of patients who underwent HPST became worse due to chemotherapy side effects and to acute complications after the transplant, such as: gastrointestinal complications, oral mucositis, veno-occlusive disease, and GVHD (25) .…”
Section: Discussionmentioning
confidence: 70%
“…In a study with post-transplant children and adolescent, pain was found to be the most frequent and debilitating symptom in the context of HPST (24) , and, in this study, it was mostly associated with oral mucositis, although it was also related with abdominal pain, to the insertion of the semi-implanted central venous catheter (SICVC), and to the graft-versus-host disease (GVHD). These results are similar to the findings of another study with a similar population, which showed that the pain of patients who underwent HPST became worse due to chemotherapy side effects and to acute complications after the transplant, such as: gastrointestinal complications, oral mucositis, veno-occlusive disease, and GVHD (25) .…”
Section: Discussionmentioning
confidence: 70%
“…Likewise, other evidence reports that the pain experienced by children and adolescents with cancer causes an unpleasant sensation, of a multi-factor origin, which is difficult to manage, and may lead to physical and emotional changes (11,12,39). Thus, the management of pain represents a challenge for professionals who work in the area, especially in its identification and management prior to the cancer treatment to which this population is submitted (13)(14)(15)39).…”
Section: Discussionmentioning
confidence: 99%
“…Segundo uma revisão integrativa sobre pacientes oncológicos pediátricos (SOUSA et al, 2019), suplementos dietéticos podem ser potencialmente prejudiciais à saúde no que tange a interação medicamentosa. Essa questão diz respeito à segurança do paciente, apontando a necessidade das instituições/profissionais de saúde passarem a realizar processos mais seguros para uma redução de danos evitáveis.…”
Section: (A) Tipos De Terapias Mais Usadas Em Crianças Com Condições ...unclassified
“…Os artigos que discorrem sobre o uso da aromaterapia possuem o objetivo de controlar a dor e melhorar a qualidade de vida das crianças em condições crônicas, o que é validado em um estudo (SOUSA et al, 2019), que traz o uso do óleo essencial de bergamota como um ansiolítico e antiemético natural para crianças, tendo efeitos positivos sobre a ansiedade e na redução da dor.…”
Section: (A) Tipos De Terapias Mais Usadas Em Crianças Com Condições ...unclassified